2012
DOI: 10.4103/0019-5278.111750
|View full text |Cite
|
Sign up to set email alerts
|

Integrated healthy workplace model: An experience from North Indian industry

Abstract: Background:Keeping in view of rapid industrialization and growing Indian economy, there has been a substantial increase in the workforce in India. Currently there is no organized workplace model for promoting health of industrial workers in India.Objective:To develop and implement a healthy workplace model in three industrial settings of North India.Materials and Methods:An operations research was conducted for 12 months in purposively selected three industries of Chandigarh. In phase I, a multi-stakeholder wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…Several reports of studies of workplace interventions to reduce NCD risk in India have demonstrated feasibility [100] and efficacy [103]. These discussions have generally focused on wellness to the exclusion of OSH [106], providing little foundation for building the OSH infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports of studies of workplace interventions to reduce NCD risk in India have demonstrated feasibility [100] and efficacy [103]. These discussions have generally focused on wellness to the exclusion of OSH [106], providing little foundation for building the OSH infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Today, a growing body of evidence supports the effectiveness of workplace interventions that integrate health protection and health promotion programs. [31][32][33] More researchers and policymakers have recognized that occupational and non-occupational factors may contribute to worker safety and health simultaneously. 34,35 In response, the National Institute for Occupational Safety and Health (NIOSH) launched the Total Worker Health TM (TWH TM ) program.…”
Section: Introductionmentioning
confidence: 99%
“…Such efforts are uncommon within India, although policy leaders and Indian employers alike are increasingly examining the implications of non-communicable diseases (NCD) and risk-related behaviours such as tobacco use for productivity and economic growth. [13][14][15][16][17] WHO, 18 the US National Institute for Occupational Safety and Health (NIOSH), 19 and others 20 21 have recommended new models for workplace interventions that aim to reduce hazards in the physical and psychosocial work environments, while also providing support for individual behavioural changes such as quitting tobacco use. This approach has been shown to be efficacious in promoting smoking cessation, particularly for bluecollar workers who face dual health risks because of their high rates of risk-related behaviours, such as tobacco use, and exposures to occupational hazards.…”
Section: Introductionmentioning
confidence: 99%